2012
DOI: 10.1113/expphysiol.2012.067967
|View full text |Cite
|
Sign up to set email alerts
|

Intense intermittent exercise provides weak stimulus for vascular endothelial growth factor secretion and capillary growth in skeletal muscle

Abstract: New Findings r What is the central question of this study?Does intense intermittent exercise provide a sufficient angiogenic stimulus to induce capillary growth in skeletal muscle conditioned by moderate intensity exercise training? r What is the main finding and its importance?We show that higher levels of shear stress and metabolism associated with intense exercise do not provide further stimulus for capillary growth. Instead, secretion of vascular endothelial growth factor and proliferation of endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
114
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(124 citation statements)
references
References 40 publications
8
114
2
Order By: Relevance
“…Moreover, peroxisome proliferator-activated γ-receptor co-activator (PGC-1α), an important regulator of both angiogenesis and mitochondrial biogenesis, was also increased to the same extent in the two training protocols. These findings are interesting, because activation of PGC-1α and subsequent mitochondrial biogenesis is largely intensity dependent (Oliveira et al 2014), whereas angiogenesis appears to be hampered when intensity gets too high (Høier et al 2013). As such, recent reports have shown that increasing the number of all-out efforts while reducing total training volume has a negative impact on skeletal muscle VEGF levels and ultimately capillarization (Gliemann et al 2015).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, peroxisome proliferator-activated γ-receptor co-activator (PGC-1α), an important regulator of both angiogenesis and mitochondrial biogenesis, was also increased to the same extent in the two training protocols. These findings are interesting, because activation of PGC-1α and subsequent mitochondrial biogenesis is largely intensity dependent (Oliveira et al 2014), whereas angiogenesis appears to be hampered when intensity gets too high (Høier et al 2013). As such, recent reports have shown that increasing the number of all-out efforts while reducing total training volume has a negative impact on skeletal muscle VEGF levels and ultimately capillarization (Gliemann et al 2015).…”
mentioning
confidence: 96%
“…As such, recent reports have shown that increasing the number of all-out efforts while reducing total training volume has a negative impact on skeletal muscle VEGF levels and ultimately capillarization (Gliemann et al 2015). Specifically, it has been shown that the angiogenic potency of an interval-based training session is less than that of a continuous moderate-intensity training session (Høier et al 2013). This has been shown over the past few years in various sports, including running, cycling, and soccer, and in both untrained, moderately trained, and elite athletes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry was performed as previously described in detail (23). Briefly, sections were rinsed and incubated with a primary antibody against CD-31 (endothelial cell marker, M0822, DakoCytomation, Glostrup, Denmark) and myosin heavy chain (MHC) antibodies against MHC I (M8421, Sigma, St. Louis, MO) and MHC IIa (N2.261, Developmental Studies Hybridoma Bank, University of Iowa).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…TIMP-1 inhibits degradation of the extracellular matrix by inhibiting matrix metalloproteinases (MMPs) and may thereby limit capillary growth (3,62). The expression of TIMP-1 in skeletal muscle is sensitive to muscle activity where acute exercise transiently increases TIMP-1 mRNA levels (23) and endurance training leads to elevated TIMP-1 protein content (21).…”
mentioning
confidence: 99%